γ-PS-functions in topological spaces - Asaad, Baravan A.; Ahmad, Nazihah; Omar, Zurni (HIKARI Ltd, 2014)
This paper introduces some new classes of functions called γ-PScontinuous, β-PS-open and β-PS-closed using γ-PS-open set and γ-PSclosed set.In addition, some properties and characterizations of these functions are given.The result shows that γ-PS-continuous function and γ-continuous function are independent.